In utero Exposure to Atrazine Disrupts Rat Fetal Testis Development - Fang, Yinghui; Ni, Chaobo; Dong, Yaoyao; Li, Huitao; Wu, Siwen; Li, Xiaoheng; Lv, Yao; Huang, Tongliang; Lian, Qingquan; Ge, Ren-shan (Frontiers in Pharmacology, 2018)
Atrazine (ATR) is a commonly used agricultural herbicide and a potential endocrine disruptor that may cause testicular dysgenesis. The objective of the present study was to investigate the effects of atrazine on fetal testis development after in utero exposure. Female Sprague-Dawley rats were gavaged daily with vehicle (corn oil, control) or atrazine (25, 50, and 100 mg/kg body weight/day) from gestational day 12 to 21. Atrazine dose-dependently decreased serum testosterone levels of male pups, with a significant difference from the control recorded at a dose of 100 mg/kg. In addition, atrazine significantly increased fetal Leydig cell aggregation at a dose of 100 mg/kg. Atrazine increased fetal Leydig cell number but not Sertoli cell number. However, atrazine down-regulated Scarb1 and Cyp17a1 in the fetal Leydig cell per se and Hsd17b3 and Dhh in the Sertoli cell per se. These results demonstrated that in utero exposure to atrazine disrupted rat fetal testis development.